2018
DOI: 10.1021/acs.iecr.8b01701
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Optimal Cleaning Scheduling and Control of Heat Exchanger Networks Undergoing Fouling: Model and Formulation

Abstract: The performance and operability of heat exchanger networks (HENs) is strongly affected by fouling, which involves the deposition of unwanted material, which reduces the heat-transfer rate and increases the pressure drop, the operational costs, and the environmental impact of the process. Periodical cleaning and control of the flow rate distribution in the HEN are used to mitigate the effects of fouling and restore the performance of the units. The optimal cleaning scheduling has been formulated as a mixed-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…A preheat train model must include individual exchangers and how they are connected in a network. As detailed in [16] a HEN is defined as a multigraph that describes the nodes, the connections between them, and the direction of flow among the nodes for different streams. Nodes are classified as sources ( ), sinks ( ), flow splitters ( ), flow mixers ( ), and exchangers ( ).…”
Section: Heat Exchanger Network and Fouling Rate Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…A preheat train model must include individual exchangers and how they are connected in a network. As detailed in [16] a HEN is defined as a multigraph that describes the nodes, the connections between them, and the direction of flow among the nodes for different streams. Nodes are classified as sources ( ), sinks ( ), flow splitters ( ), flow mixers ( ), and exchangers ( ).…”
Section: Heat Exchanger Network and Fouling Rate Modelsmentioning
confidence: 99%
“…Model B: this simpler, radially-distributed but axially-lumped parameter exchanger model (hence, 1 D-distributed) considers the overall effect of the exchanger inputs on the outputs, without much detail for the heat transfer or deposit distribution inside the unit. The model, detailed in [16] is based on the P-NTU approach [32] and the definition of the P-efficiency (the actual heat transfer in the exchanger with respect to the maximum possible heat transfer), which is related to the number of transfer units and the exchanger geometry. The time evolution of the system is given by the fouling/ageing model, and at every time a steady state algebraic model for the exchangers determines the outlet streams temperature and pressure.…”
Section: Heat Exchanger Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, various approaches to the mitigation of fouling effects in industrial HEs and HENs have been reported in the literature [3,4]. Fouling leads to the reduction of steady-state heat recovery [5], but also to changes in the transient states of HEs [6] and inefficient control of HEs [7,8] that may have an adverse effect on the overall performance of the HEN [9,10]. In the literature, publications devoted to the effect of fouling on the dynamic behavior of HEs and the role of fouling in control issues are rare and limited in scope [11,12].…”
Section: Introductionmentioning
confidence: 99%